Palestine in Indonesian Media: Framing the Israeli-Palestinian Conflict and Its Impact on Public Perception (Palestine Issues on Indonesian Society, 2024)
This paper examines how Palestinian issues are framed in Indonesian media and the implications of these representations on public perceptions of the Israeli-Palestinian conflict. The study analyzes coverage of Palestine in mainstream media, including newspapers, television, and social media platforms, with a focus on the framing techniques used to portray the conflict. Using a media analysis framework, the paper explores how narratives of resistance, justice, and victimhood shape public understanding of the Palestinian struggle and the Israeli occupation. Additionally, the study looks at how Indonesian media portray the role of international actors, particularly the United States and Israel, in exacerbating the conflict. It also assesses the role of social media in mobilizing public opinion, especially among younger generations. By examining the media's role in shaping both public opinion and political discourse, this paper provides insights into how media framing influences national sentiment toward Palestine.